2023
DOI: 10.1126/sciimmunol.add1153
|View full text |Cite
|
Sign up to set email alerts
|

STING-activating nanoparticles normalize the vascular-immune interface to potentiate cancer immunotherapy

Abstract: The tumor-associated vasculature imposes major structural and biochemical barriers to the infiltration of effector T cells and effective tumor control. Correlations between stimulator of interferon genes (STING) pathway activation and spontaneous T cell infiltration in human cancers led us to evaluate the effect of STING-activating nanoparticles (STANs), which are a polymersome-based platform for the delivery of a cyclic dinucleotide STING agonist, on the tumor vasculature and attendant effects on T cell infil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 71 publications
0
20
0
Order By: Relevance
“…For this reason, hypoxia and acidosis produced in the TME trigger the production of immunosuppressive factors, inhibiting immune cell recruitment, extravasation, and antitumor effector functions. 124 The important role of tumor vasculature in tumor progression makes it an attractive target for cancer therapy. The above studies have shown that tumor vascular normalization can improve blood perfusion, alleviate tumor hypoxia, increase the infiltration of immune effector cells into tumor tissues, transform the immunosuppressive TME into immunomodulatory, and ultimately enhance the efficacy of immunotherapy.…”
Section: Regulation Of Abnormalmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, hypoxia and acidosis produced in the TME trigger the production of immunosuppressive factors, inhibiting immune cell recruitment, extravasation, and antitumor effector functions. 124 The important role of tumor vasculature in tumor progression makes it an attractive target for cancer therapy. The above studies have shown that tumor vascular normalization can improve blood perfusion, alleviate tumor hypoxia, increase the infiltration of immune effector cells into tumor tissues, transform the immunosuppressive TME into immunomodulatory, and ultimately enhance the efficacy of immunotherapy.…”
Section: Regulation Of Abnormalmentioning
confidence: 99%
“…Tumor vasculature is often malformed and dysfunctional, characterized by a leaky network of immature microvessels with disorganized, reduced peripheral cell support. For this reason, hypoxia and acidosis produced in the TME trigger the production of immunosuppressive factors, inhibiting immune cell recruitment, extravasation, and antitumor effector functions . The important role of tumor vasculature in tumor progression makes it an attractive target for cancer therapy.…”
Section: Application Of Tumor Microenvironment Modulated Nanoplatform...mentioning
confidence: 99%
“…8 However, the transient alleviation of hypoxia fails to address the underlying issue of increased O 2 consumption resulting from the rapid proliferation of tumor cells. 9 Conversely, it possesses the potential to induce the risk of promoting tumor cell proliferation and recurrence. 1,10 Recent studies have provided evidence that even a slight reduction in the oxygen consumption rate (OCR) was more effective in alleviating hypoxia, owing to an increase the oxygen partial pressure (PO 2 ) within both tumor microvessels and tumor tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxia, a pervasive characteristic in solid tumors, could disrupt DNA damage repair pathways and suppress intratumor heterogeneity as well as immune responses, thereby facilitating tumor progression and metastasis. Hypoxia arises from the imbalance between the heightened oxygen (O 2 ) demand triggered by rapid proliferation of tumor cells and the inadequate oxygen supply due to the aberrant and compromised tumor vascular system. Enhancing the O 2 supply, which is achieved either by direct generation of O 2 at the tumor site or normalization of disordered tumor vasculature to enhance oxygen delivery, represents the primary strategy for alleviating tumor hypoxia . However, the transient alleviation of hypoxia fails to address the underlying issue of increased O 2 consumption resulting from the rapid proliferation of tumor cells . Conversely, it possesses the potential to induce the risk of promoting tumor cell proliferation and recurrence. , Recent studies have provided evidence that even a slight reduction in the oxygen consumption rate (OCR) was more effective in alleviating hypoxia, owing to an increase the oxygen partial pressure (PO 2 ) within both tumor microvessels and tumor tissues. ,, The primary oxygen consumption in tumor cells is attributed to the mitochondrial oxidative phosphorylation (OXPHOS) for adenosine triphosphate (ATP) generation. ,, Therefore, inhibition of the electron transport chain (ETC), which is the crucial process in OXPHOS, presents a more efficacious strategy for alleviating tumor hypoxia by reducing the OCR. …”
Section: Introductionmentioning
confidence: 99%
“…Cancer nanotechnology refers to the application of nanotechnology to diagnose , or treat cancer, and various nanoparticles are making headway through preclinical and clinical development . A key step in drug development is investigating pharmacology and safety.…”
mentioning
confidence: 99%